2010
DOI: 10.1002/jbt.20339
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of combination of quercetin and α‐tocopherol on mitochondrial dysfunction and myocardial infarct size in isoproterenol‐treated myocardial infarcted rats: Biochemical, transmission electron microscopic, and macroscopic enzyme mapping evidences

Abstract: Mitochondrial dysfunction plays an important role in the pathology of myocardial infarction. We evaluated the combined protective effects of quercetin and α-tocopherol on mitochondrial damage and myocardial infarct size in isoproterenol-induced myocardia- infarcted rats. Rats were pretreated with quercetin (10 mg/kg) alone, α-tocopherol (10 mg/kg) alone, and combination of quercetin (10 mg/kg) and α-tocopherol (10 mg/kg) orally using an intragastric tube daily for 14 days. After pretreatment, rats were induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Therapeutic intervention that could improve impaired antioxidant defense mechanisms or diminish free radical production in the ischemic myocardium has been of great interest 16. Previously, we reported the combined protective effects of quercetin and α‐tocopherol on lipids, glycoprotein components, and mitochondrial dysfunction in ISO‐treated rats 17,18. Quercetin and α‐tocopherol are abundantly present in vegetables and fruits, and these are daily consumed in our diet.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic intervention that could improve impaired antioxidant defense mechanisms or diminish free radical production in the ischemic myocardium has been of great interest 16. Previously, we reported the combined protective effects of quercetin and α‐tocopherol on lipids, glycoprotein components, and mitochondrial dysfunction in ISO‐treated rats 17,18. Quercetin and α‐tocopherol are abundantly present in vegetables and fruits, and these are daily consumed in our diet.…”
Section: Introductionmentioning
confidence: 99%
“…Amelioration of lysosomal enzymes was implicated behind the observed protection . In another study, electron microscopy-based investigations showed significant improvements of mitochondrial structure and correlated with biochemical results (Punithavathi & Stanely Mainzen Prince, 2010). Li et al proved that quercetin provides superior cardioprotective effects compared with its glycoside derivative rutin.…”
Section: Citrus Sp (Quercetin)mentioning
confidence: 84%
“…Recently, a study published by Punithavathi and Prince. 4 suggested that intake of quercetin and α-tocopherol and other dietary supplements offers protection against ISO-induced mitochondrial damage by increasing the activities of mitochondrial enzymes in rats. Our results are consistent with the observation of Khatua et al 40 where garlic and diallyl disulfide functioned as a scavenger of toxic reactants and increased the activities of Kreb cycle enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…3 Thus, ROS generation in large amounts leads to structural changes and myocardial necrosis of the heart tissue. Punithavathi and Prince 4 reported that the lack of oxygen supply during infarction caused damage to the mitochondrial ETC, which results in accumulation of toxic metabolites, adenosine triphosphate (ATP) depletion, intracellular Ca 2+ overload, mitochondrial membrane depolarization, mitochondrial swelling, and finally cell death.…”
Section: Introductionmentioning
confidence: 99%